Literature Review: The Role of Quizizz Media in Improving Science Learning Outcomes of Fifth Grade Elementary School Students - Oky Wulandari; Nurulul Fatimah; Agustin Arum Setiyana (Schola, 2026)
These The current technological era presents new challenges in the world of education, including in the learning process which necessitates the use of diverse digital platforms like Quizizz. The objective of this research is to conduct a literature analysis related to the utilization of Quizizz as a learning tool and evaluation instrument at the elementary school level. This study employed a systematic literature review through five steps: topic determination, article searching, article selection, literature analysis, and conclusion drawing. This research analyzed 24 articles relevant to the focus of the study, which is the use of Quizizz in elementary school learning. These articles were selected and published between 2019 and 2024. The findings from the literature review indicate that: 1) The Quizizz platform is designed as a learning tool because it offers presentation features with various attractive displays, making it more interactive. 2) Generally, Quizizz is used as an evaluation tool, providing numerous assessment features such as multiple-choice questions, open-ended questions, matching questions, and categorization questions. Furthermore, this platform also offers flexible assessments with possible answers including images, videos, and audio. 3) The use of the Quizizz platform generally has a positive impact on improving student learning outcomes; in other words, students' understanding tends to increase after learning material using Quizizz. Additionally, the utilization of Quizizz also contributes to students' learning motivation, enthusiasm, and skill development. Thus, Quizizz becomes a crucial platform for educators in creating innovative Science (IPA) learning to enhance various skills and prepare students to face the challenges of the times and technological advancements.